New campus-Keats building-0001
Student Owned and operated, the Bookstore is one of the most modern building of it type in the State of California. The students serves him or herself in finding books, supplies, and other accessories necessary for academic living. The latest in inter-office communications and music for customer's pleasure is available in the $100,000 structure.